(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Coarctation of the aorta (CoA) represents a congenital cardiac anomaly characterized by narrowing of the aortic lumen, often leading to significant hemodynamic alterations and subsequent cardiac complications. Among these complications, left ventricular (LV) dysfunction emerges as a critical concern, particularly in infants under one year of age. Understanding the trigger factors for LV dysfunction in this specific population is paramount for timely intervention and improved patient outcomes.